PELATIHAN DASAR-DASAR KEAMANAN AIR BAGI PENGAWAS KOLAM RENANG (LIFEGUARD) Se-DIY - Susanto, Ermawan (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2009)
Abstract The goal of this water safety training is to give basic skill and knowledge about water safety for 25 members of lifeguard in Special Province of Jogjakarta. The method that was used for this training were workshop, discussion, simulation, training in water, and evaluation test method. Evaluation with direct observation consists of attention, willingness, enthusiasm to the matery who was given by society servants team (PPM), and post test for the last. Then, evaluation in the pool with several activities that were helping drawning victims by equipment and no equipment, giving mouth to mouth breath, cardiopolmunory respiration, bouancy test, diving test, and swimming rescue. This training followed by 25 Jogjakarta’s lifeguards and they were 2 from Sleman, 2 from Bantul, 8 from Jogja city, 6 from Gunungkidul and 5 FIK’s students. The result of discusion are (1) there are many swimming pool that don’t have rescue equipment like lifejacket, rope, stick, and wheel. (2) there is less knowledge about rescue swimming technique for the lifeguard in Jogjakarta., (3) there are many swimming pool which have no life guard, (4) we have high rate entusiasm of participant, and (5) we also have good management in swimming pool. Keywords: water accident, water safety, and life guard